The Quantum Entropy as an Ultimate Visiting Card of the de Broglie–Bohm Theory - Fiscaletti, D. (Ukrainian Journal of Physics, 2012)
The de Broglie–Bohm theory is an interesting approach to quantum mechanics, which has the merit to describe atomic and subatomic processes without ascribing a special role to the observer and remaining faithful to the principle of causality and the motion dogma. In this article, a new suggestive interpretation of the de Broglie–Bohm theory is proposed. It is based on the idea that the quantum entropy is its ultimate visiting card in the quantum domain, in a relativistic curved space-time, and in the quantum gravity domain.